The Child Life Challenges Scale (CLCS): Associations of a Single-Item Rating of Global Child Adversity with Children's Total Life Stressors and Parents' Childhood Adversity - Jillian S. Merrick; Madelyn H. Labella; Angela J. Narayan; Christopher D. Desjardins; Andrew J. Barnes; Ann S. Masten (MDPI AG, 2020)
Background: Although many existing measures tabulate specific risk factors to yield cumulative risk indices, there is a need for low-burden strategies to estimate general adversity exposure. Aims and Methods: This study introduces a brief, new measure of lifetime adversity, the Child Life Challenges Scale (CLCS), and examines its validity in a sample of parents and children residing in emergency housing. The CLCS comprises a single global item for rating cumulative life challenges utilizing either a paper-pencil scale or a sliding scale on a tablet. Parents are provided with anchor examples of mild and extreme challenges and asked to mark a location along the scale reflecting number and severity of challenges in their children's lives to date. Study participants included 99 parents and their 3- to 6-year-old children. Results: CLCS scores were moderately associated with children's parent-reported total life stressors, and these associations were robust to controls for parental history of adversity, parental distress, and family demographics. Control variables also did not moderate associations between CLCS scores and total life stressors, suggesting that the CLCS functions similarly across a range of sociodemographic risk. Paper-pencil and tablet versions showed similar convergent validity. Conclusion: The CLCS shows promise as an efficient measure for estimating children's lifetime adversity with minimal parent or administrator burden.